Difficulties facing the teaching of physical education and its profess ional teachers in education schools up in Lattakia Governorate-2024- (Journal of Hama University, 2026)
The study aimed to identify the degree of professional difficulties faced by male and female physical education teachers in secondary education schools in Lattakia GovernorateIn order to achieve the aim of the study, the study was conducted on a sample of (92) teachers and schools. A questionnaire was applied to them, which included (44) items and was distributed into five areas،The area of ​​school administration (11) items, the area of ​​students (8) items, the area of ​​co-workers (8) items, the area of ​​sports equipment and equipment (9) items, the area of ​​professional development (8) items،The results of the study indicated that the degree of overall professional difficulties was very large in most fields. Accordingly, the researcher recommended several recommendations that suit the difficulties found in these fields.
Keywords: professional difficulties; secondary schools; physical education teacher